Adenosine Triphosphate Production of Muscle Mitochondria after Acute Exercise in Lean and Obese Humans - Kras, Katon A; Hoffman, Nyssa; Roust, Lori R; Benjamin, Tonya R; DE Filippis, Elena A; Katsanos, Christos S (Medicine and science in sports and exercise, 2019)
Current evidence indicates mitochondrial dysfunction in humans with obesity. Acute exercise appears to enhance mitochondrial function in the muscle of nonobese humans, but its effects on mitochondrial function in muscle of humans with obesity are not known. We sought to determine whether acute aerobic exercise stimulates mitochondrial function in subsarcolemmal (SS) and intermyofibrillar (IMF) mitochondria in humans with obesity. We assessed maximal adenosine triphosphate production rate (MAPR) and citrate synthase (CS) activity in isolated SS and IMF mitochondria from subjects with body mass index < 27 kg·m (median age, 25 yr; interquartile range, 22-39 yr) and subjects with body mass index > 32 kg·m (median age, 29 yr; interquartile range, 20-39 yr) before and 3 h after a 45-min cycling exercise at an intensity corresponding to 65% HR reserve. The SS and IMF mitochondria were isolated from muscle biopsies using differential centrifugation. Maximal adenosine triphosphate production rate and CS activities were determined using luciferase-based and spectrophotometric enzyme-based assays, respectively. Exercise increased MAPR in IMF mitochondria in both nonobese subjects and subjects with obesity (P < 0.05), but CS-specific activity did not change in either group (P > 0.05). Exercise increased MAPR supported by complex II in SS mitochondria, in both groups (P < 0.05), but MAPR supported by complex I or palmitate did not increase by exercise in the subjects with obesity (P > 0.05). Citrate synthase-specific activity increased in SS mitochondria in response to exercise only in nonobese subjects (P < 0.05). In nonobese humans, acute aerobic exercise increases MAPR in both SS and IMF mitochondria. In humans with obesity, the exercise increases MAPR in IMF mitochondria, but this response is less evident in SS mitochondria.